Florística vascular não arbórea de um fragmento de floresta estacional semidecidual no munícipio de Analândia - SP - Dinato, Daniela de Oliveira [UNESP] (2014)
(Nontrees Vascular Floristic of a fragment of Semideciduous Seasonal Forest in the municipality of Analândia - SP). The Rawistcher Park is located in Pedra Vermelha farm, in the city of Analândia, central-eastern region of São Paulo state, between the coordinates 22°06’53’’- 05’35’’S and 47°46’06’’- 45’14’’W. It is a Semideciduous Seasonal Forest fragment of about 80 ha that occurs on basaltic cuestas. This study aimed to conduct inventory of the nontrees (shrubs, ground herbs, epiphytes, climbers) vascular flora (including pteridophytes s.l.) of the area. Samplings were conducted from April 2012 to December 2013 using the method of traversal on trails. The nontrees flora of Rawistcher Park consists of 230 species belonging to 74 families, 89% angiosperms and 11% pteridophytes s.l. Asteraceae was the fanerogamic family with the highest number of species (17), followed by Piperaceae (13), Malvaceae (12), Rubiaceae (11), Cyperaceae (10) Solanaceae, Poaceae and Fabaceae (9), Bignoniaceae (8) and Orchidaceae (7). Polypodiaceae was the more representative family of Pteridophytes s.l. (5). Nontree flora represents above 53% of total know flora of Rawistcher Park. Regarding the life form, most are herbs (48%), followed by shrubs (23%), climbers (22%) and epiphytes (7%). Among all species, 19 are endemic to the Atlantic Forest and nine are non-native from brazilian flora. Six species of this survey are considered threatened or near threatened with extinction, according to the Red List of endangered species in the state of São Paulo. Compared with other floristic surveys, the results show a high local floristic richness and emphasize the heterogeneity and particularity of each forest fragment of São Paulo state, confirming the importance of its preservation